Correlation between GRIK2 rs6922753, rs2227283 polymorphism and aggressive behaviors with Bipolar Mania in the Chinese Han population - Haibo Ma; Guanglei Xun; Renyun Zhang; Xiaohua Yang; Yu Cao (Brain and Behavior, 2019)
Abstract Objectives Animal studies have shown that glutamate receptor ionotropic kainate 2 (GRIK2) gene knockout mice are more impulsive and aggressive. This study aims to verify whether the rs6922753 and rs2227283 polymorphisms of the GRIK2 gene are associated with both aggressive behavior and bipolar mania in the Chinese Han population. Methods Polymerase chain reaction (PCR) was applied in the genotype rs6922753 and rs2227283 polymorphisms of the GRIK2 gene in 201 bipolar manic patients with aggressive behaviors, 198 bipolar manic patients without aggressive behaviors, and 132 healthy controls. The Modified Overt Aggression Scale (MOAS) was used to evaluate aggressive behavior in patients with bipolar mania. Results No correlation was found between aggressive behavior and the rs6922753 polymorphism in the three groups. The A/A genotype and A allele of the rs2227283 polymorphism were found significantly more frequently in patients with aggressive behavior than in healthy controls (p = .004 and p = .013, respectively) and in patients with nonaggressive behavior (p = .002 and p = .018, respectively). The A/A genotype and A allele were associated with an increased risk of aggressive behavior. Conclusion This study suggests that the rs2227283 polymorphism of the GRIK2 gene is related to aggressive behaviors in bipolar manic patients and that the A/A genotype and A allele may increase the risk of the aggressive behavior in bipolar manic patients.